DEMENTIA-SPECIFIC STAFF TRAINING: VARIATION AND TRENDS IN U.S. ASSISTED LIVING STATE POLICIES - Smith, L (Innov Aging, 2018)
As assisted living communities assume an increased role in providing long-term services to older persons with Alzheimer’s disease and related disorders (ADRD), there is an urgent need to understand the positive and negative effects of state regulations on quality of care. Prior research indicates that the qualifications of staff who work with persons who have ADRD is associated with resident outcomes, satisfaction, and overall well-being. This poster describes findings from an ongoing study that aims to document the impact of state regulations on resident outcomes. Specifically, we present analysis based on a regulatory review of states’ staff training requirements for dementia care. The sample includes all 50 states and the District of Columbia. Current regulations were collected and analyzed via a qualitative coding schema. We found that 23 states have regulations that require dementia-specific training, and 22 states require dementia-specific continuing education. Nearly all states (49) require that administrators complete dementia-specific training. Of these, 13 states specified between 7 and 120 hours of dementia care training. The poster presentation describes state variation in direct care staff training requirements, including: number of training hours, training content, use of examinations or other tests of knowledge, skills and abilities. These learnings may inform future research as well as policies and recommendations for assisted living settings serving people with ADRD. This presentation is part of the ongoing study: Do State Regulations Affect the Outcomes of Assisted Living Residents with Dementia? (Thomas, K. R01AG057746)